Konsentrat Serat Kedelai : Preparasi dan Pengaruhnya terhadap Sifat Fisik dan Kimia Digesta pada Tikus - Sri Budi Wahjuningsih; Yustinus Marsono; Zuheid Noor (agriTECH, 2005)
Soy fiber concentrate (SFC) was isolated from soy flour by extraction in alkali solution (pH 9), centrifuged and washed the solid in ethanol 80% then in acetone 33%, and dried. Effects of soy fiber diet on physical and chemical properties of the rat digesta were evaluated. The objective of this study were (I) to determine the composition of the SFC , (2) to evaluate the effect of soy fiber diets on physical properties (water content and weight) and chemical properties ( pH and SCFA) of the caecal digesta in rats. Four groups of jive male Sprague Dawley rats were provided. They were given differ rent diets Le. soybean, low and high soybean fiber and control diets ad libitum for 21 days period. In the end of experiment they were killed, the caecum were cut and the caecal digesta were taken and analyzed for moisture content, weight, pH and SCFA concentrations. It was found that soy fiber concentrate contains 71.52% total dietary fiber (62.56% insoluble fiber and 8.96 soluble fiber). Weight and moisture contents of the digesta were not affected by the soyfiber diets, but the diets decreased the pH of the digesta significantly. The diet also did not affect the molar proportion of the SCFA. SCFA molar ratio of the caecal digesta were: 62-63: 26-27: 10-11 for acetic: propionic: butyric acid